Marketing Strategies for Enhancing New Student Enrollment: A Multi-Case Study of Bustanul Muta’alimin and Nurul Ulum Islamic Boarding Schools in Blitar City - Habibur Rahman; Yatim Rianto; Ngainun Naim; Nur Efendi; Winarto (Technium Social Sciences Journal, 2025)
The marketing of educational services, once deemed inappropriate due to its perceived commercial and profit-oriented nature, has become increasingly transparent and accepted. Education plays a pivotal role in the development and enhancement of human resources, and the existence of high-quality educational institutions is a shared aspiration, as they are instrumental in producing competent individuals capable of driving meaningful societal transformation. Within the context of educational services, marketing is understood as a social and managerial process aimed at fulfilling needs and desires through the creation and exchange of valuable educational offerings. This study aims to explore and analyze the promotional strategies implemented by Bustanul Muta’alimin Islamic Boarding School and Nurul Ulum Islamic Boarding School in Blitar City in their efforts to increase new student enrollment. Employing a qualitative approach with a multi-case study design, data were collected through in-depth interviews, participant observation, and documentation. Data analysis was conducted using the Miles, Huberman, and Saldana model, encompassing data condensation, data display, verification, and conclusion drawing. The trustworthiness of the data was ensured through credibility, transferability, dependability, and confirmability procedures. The findings of the study reveal that the promotional strategies employed to increase new student enrollment involve a variety of approaches—mass, personal, and digital—utilizing both online and traditional media. Specifically, these strategies include: promotion through the structural networks of Nahdlatul Ulama (NU), word-of-mouth (WOM) marketing, alumni network promotion, maximizing the use of digital technology, the use of large-scale billboard advertisements, and the influential role of Islamic scholars (kiai) as promotional figures.